Simultaneous MMW generation and up-conversion for WDM-ROF systems based on FP laser. (October 2016) - Zhang, Chan; Ning, TiGang; Li, Jing; Li, Chao; He, Xueqing; Pei, Li
Abstract: A new wavelength division multiplexing radio-over-fiber (WDM-ROF) scheme based on Fabry-Perot (FP) laser is proposed and demonstrated for simultaneous millimeter-wave (MMW) generation and up-conversion. The tunable optical comb generated by FP laser is served as a cost-effective WDM optical source in central station (CS) and it makes all-optical up-conversion process for all channels simple compared with using a DFB array. All modes from the FP laser are modulated simultaneously by a LiNbO3 Mach-Zehnder modulator (LN-MZM) then. We have systematically compared the performances of MMW generation and up-conversion using LN-MZM based on different modulation schemes. A reflective semiconductor optical amplifiers (RSOA) is used both for the downstream modulation of each channel and for the reduction of mode partition noise (MPN) induced from FP laser. In the scheme, the multiple optical carrier suppression (OCS) modulation shows the highest receiver sensitivity and smallest power penalty over long-distance delivery. In the numerical simulation, 7 WDM channels each carrying 2.5 Gb/s baseband signal have been up-converted to 60 GHz simultaneously with good performance over 25 km single mode fiber (SMF) transmission. Highlights: A novel optical up-conversion for WDM-ROF transmission is proposed. A single FP laser is served as a cost-effective WDM optical source in CS. Different performances based on different modulation scheme is studied. 7 WDM channels have been up-converted to 60 GHz simultaneously with good BER. The scheme is a simple cost-efficient for optical-wireless access communication.